(3GdeNJGQ ef TYQ CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3Chdg ef bUjOI jeOM HgG GdeCehf Oef Cde HgG abGd SdGe ce Md YbOI UHQg GdEdeGe s
(3BNQgG (B:s
(3adjHdZ GdaJjGf Yfi eGdcG Cfi eJi jJKdehG CJgOe JeJ GdeNJGQGJ ef OjhGf CHj JeGe GdWGFi , hgj Cda hSJI hSHYhf HjJkG hGdMeeO ddg JYGdi Mb MeOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3OjhGf TYQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3COH (B34) s
Keywords: (3GdCOHs